Biofuel from hydrocracking of Cerbera manghas oil over Ni-Zn/HZSM-5 catalyst - Marlinda, Lenny; Prajitno, Danawati Hari; Roesyadi, Achmad; Gunardi, Ignatius; Mirzayanti, Yustia Wulandari; Al Muttaqii, Muhammad; Budianto, Agus (Eclética Química, 2022)
The effects of reaction temperature on the hydrocarbon composition of biofuel produced in hydrocracking of Cerbera manghas oil with Ni-Zn/HZSM-5 catalyst were investigated. The incipient wetness impregnation method was applied to prepare the Ni-Zn/HZSM-5 catalysts. Furthermore, the properties of catalysts were measured by X-ray diffraction, atomic absorption spectrometry, and nitrogen physisorption. Hydrocracking process was carried out in Parr USA pressure batch reactor at pressure of 20 ± 5 bar after flowing H2 for 1 h. The reaction with a catalyst/oil ratio of 1 g/150 mL proceeded at various temperatures of 350, 375 and 400 °C for 2 h. Gas chromatography-mass spectrometry was used to analyze biofuel. The most abundant hydrocarbon compounds in biofuel were identified as pentadecane and heptadecane (a major diesel fuel compound) with a different amount at different reaction temperatures. It can be said that the hydrodecarboxylation/decarbonylation routes were the predominant reaction pathways and oxygen removal occurred during hydrocracking. The Cerbera manghas oil can be recommended as a promising biofeed to produce the gasoil as an alternative transportation fuel.